Indoor air quality improvement in COVID-19 pandemic: Review. (July 2021) - Agarwal, Nehul; Meena, Chandan Swaroop; Raj, Binju P; Saini, Lohit; Kumar, Ashok; Gopalakrishnan, N.; Kumar, Anuj; Balam, Nagesh Babu; Alam, Tabish; Kapoor, Nishant Raj; Aggarwal, Vivek
Highlights: Poor air quality increased the COVID-19 infection in indoor spaces. The current pandemic made the assessment of pollutant concentration substantial. Effectiveness of non-pharmaceutical measures including facemasks, lockdown, social distancing. A holistic study of the techniques for improvement of indoor air quality resulting in an integrated solution. Implementation of engineering control techniques for paving a way towards a sustainable future. Abstract: Introduction: The advent of COVID-19 has impinged millions of people. The increased concern of the virus spread in confined spaces due to meteorological factors has sequentially fostered the need to improve indoor air quality. Objective: This paper aims to review control measures and preventive sustainable solutions for the future that can deliberately help in bringing down the impact of declined air quality and prevent future biological attacks from affecting the occupant's health. Methodology: Anontology chart is constructed based on the set objectives and review of all the possible measures to improve the indoor air quality taking into account the affecting parameters has been done. Observations: An integrated approach considering non-pharmaceutical and engineering control measures together for a healthy indoor environment should be contemplated rather than discretizing the available solutions. Maintaining social distance by reducing occupant density and implementing a modified ventilation system with advance filters for decontamination of viral load can help in sustaining healthy indoor air quality. Conclusion: The review paper in the main, provides a brief overview of all the improvement techniques bearing in mind thermal comfort and safety of occupants and looks for a common ground for all the technologies based on literature survey and offers recommendation for a sustainable future.